Impact of rotavirus vaccine in reducing hospitalization rates in pediatric patients: a single center experience in Italy - Silvia Dettori; Ilaria Cortesia; Marcello Mariani; Anna Opisso; Alessio Mesini; Carolina Saffioti; Elio Castagnola (Human Vaccines & Immunotherapeutics, 2021)
Rotavirus is a major cause of acute gastroenteritis in children under 5 years of age, with severe illness occurring in 30–40% of cases. In Italian region of Liguria, vaccination with a two-dose human attenuated vaccine was introduced in 2013. We conducted a retrospective study to assess the impact of rotavirus vaccine on hospitalizations for rotavirus-related gastroenteritis (RVGE) at the IRCCS Istituto Giannina Gaslini. Every hospitalization due to laboratory-confirmed RVGE and acute gastroenteritis of unknown origin (AGUO) in patients aged 0–14 years in the period 2008–2019 were anonymously extracted. Vaccine coverage were obtained from the regional vaccination registry. The results were divided in 2008–2012 (before RV vaccine) and 2013–2019 (after) periods. From 2008 to 2012, there was a continuous reduction of AGUO hospitalizations while RVGE increased. Since 2013, a reduction in hospitalization rate was observed for RVGE with a sharp decrease from 17.81 per 10.000 children in 2012 to 0.79 per 10,000 in 2019, parallel with the ascending values of RV vaccination coverage that increased from 36.3% in 2013 to 63.9% in 2019. A significant negative correlation was found between the proportions of vaccinated newborns and RVGE rates (p = .012). Intussusception-related hospitalization did not show substantial modifications. We confirm vaccination as a safe practice that has a significant impact in pediatric hospitalization rates.